Return to the countryside: The return intentions of highly educated young people in the Akmola province of northern Kazakhstan - Sagyndykova, Galiya; Buchenrieder, Gertrud; Dufhues, Thomas; Möllers, Judith; Runschke, David (Wiley, 2019)
The rural out‐migration of young people leads to problems such as “brain drain” and the overageing of the rural population. The purpose of this paper is to study return migration motives among students originating from rural areas. The case study relates to the province of Akmola, northern Kazakhstan. Based on data collected from college and university students (n = 357), a binary logistic regression model is used to identify rural return motives. Noneconomic and economic motives are equally important in forming a return intention. Our findings do not suggest that particularly underperforming students intend to return. As expected, compared with those in major cities, students who study in a regional town intend to return more often. We also found a large difference in return intentions along ethnic lines. Students of non‐Kazakh decent are much more likely to return than ethnic Kazakhs, and the two ethnic groups have quite distinct motives indicating signs of ethnic discrimination against non‐Kazakhs in the job market.